Perioperative complications of the modified Stoppa approach for the treatment of pelvic bone fractures: a single-institution review of 48 cases - Hyeonjoon Lee; Suenghwan Jo; Gwangchul Lee; Yongjin Cho (Journal of Trauma and Injury)
Purpose The current study aimed to report the perioperative complications of the modified Stoppa approach for the treatment of pelvic bone fractures. Methods We analyzed 48 consecutive operations in 45 patients who were treated with internal fixation using the modified Stoppa approach between March 2016 and July 2018. This included three revision operations. The mean age of the patients was 54.5 years, and the patients included 35 male patients and 10 female patients. All fractures occurred as a consequence of high-energy trauma and 70.3% had associated injuries at the time of the fracture. The mean Injury Severity Score was 9.03±5.60. The perioperative complications found during and immediately after surgery were recorded and were classified into three categories: vascular injuries, nerve injuries, and other complications. Results Overall, 14 perioperative complications (29.2%) in 14 cases were identified. The most common complications were nerve injuries, which occurred in seven cases, all involving the obturator nerve. Uncontrollable vascular injuries occurred in six cases, which required additional incisions and support of vascular surgeons or postoperative interventions. Additionally, one case of peritoneal tearing occurred, which required help from an abdominal surgeon. Conclusions While the modified Stoppa approach seems to be a viable method to treat pelvic fractures, significant perioperative complications may occur, suggesting that surgeons should pay careful attention to minimize the damage to other structures and that appropriate support from other surgical departments is paramount.